UC-1, a new bacteriophage that uses the tonA polypeptide as its receptor. - Lundrigan, M D (1983)
We characterized UC-1, a previously undescribed Escherichia coli phage. UC-1 was observed to have an icosahedral head and a long, flexible, noncontractile tail: its genome consisted of linear double-stranded DNA having a molecular weight of 34 X 10(6). The product of the tonA gene served as at least part of the receptor for UC-1. E. coli tonA strains neither plated nor adsorbed UC-1 well, tonA mutants were selected on the basis of UC-1 resistance, and ferrichrome, a siderophore which utilizes TonA as its receptor, blocked infection. Restriction analyses, DNA-DNA hybridization experiments, and guanine-plus-cytosine determinations demonstrated that UC-1 DNA was unrelated to that of other phages (T1, T5, and phi 80) which employ TonA as a receptor. Also, mutants specifically resistant to UC-1 were isolated. UC-1 may be useful as a probe for investigating TonA, which functions as a receptor for more ligands than any other membrane protein. Study of the resistant mutants may improve our understanding of how phage DNA penetrates the cell envelope.